Enhancing Learning Outcomes in Applied Physics Through Web-Based Simulation Media - Mukhlidi Muskhir; Zakaria Zakaria; Afdal Luthfi (Postgraduate, University of Mataram, 2024)
This study aims to develop interactive web-based simulation learning media for applied physics subjects and to evaluate the validity, practicality, and effectiveness of the media in improving student learning outcomes. The research method used is Research and Development (R&D) with the ADDIE development model, which includes five stages: analysis, design, development, implementation, and evaluation. Validation was carried out by media and content experts, followed by field trials involving 69 students from SMKN 1 Bintan Utara. The research instruments used structured Likert-scale questionnaires to assess the validity, practicality, and effectiveness of the media. The validation results indicated that the learning media were valid and aligned with learning needs. The practicality test yielded an average score of 84.94%, categorized as highly practical. Effectiveness testing through gain score analysis showed an improvement in student learning outcomes, with a gain value of 0.32, categorized as moderate. In conclusion, the web-based simulation media is effective, valid, and practical in enhancing students' understanding of concepts and learning outcomes in applied physics.